Evaluation of Turkish Athletes' Awareness Regarding the Use of Mouthguards - Esra Korkmaz Torun; Merve Aydemir Kurdal; Serdar Bağlar (Current Research in Dental Sciences)
Objective: To examine the awareness of Turkish athletes about mouthguard use and to make mouthguard use routine.Methods: This cross-sectional study is aimed to determine the knowledge about the advantage of mouthguard use of athletes. Participants over the age of 18 who answered all questions were included in this study. Those who refused to participate in the survey were excluded. A face-to-face survey including 10 questions was made. The questionnaire were given on a day and collected the next day.Results: There was a significant difference between protection awareness and use of Mouthguard (P